THE CONCEPT OF PERSONAL STYLE OF PROFESSIONAL ACTIVITY OF POLICE OFFICERS - Yevtushenko, Viktoriia (PSYCHOLOGICAL JOURNAL, 2019)
This article is devoted to the concept of personal style of professional activity; it deals with theoretical analysis of the concept of «individual style of activity» in the aspect of person’s development as a subject of labor. It is noted that the studies of local and foreign scientists have completely different comprehension of the concept of individual style of activity. V. S. Merlin, E. A. Klimov, K. A. Abulhanova-Slavska, A. K. Markova, M. R. Schukina, etc have made a considerable contribution to understanding of the concept of individual style of activity. Even though it is mentioned that there are a lot of researches devoted to the theoretical and experimental studies of the issues of individual style and style of professional activity in the scientific-psychological literature, there are only few of them dedicated to the style of professional activity of police officers. Even less attention is paid to the psychological characteristics of the style of professional activity of the policemen. Under the concept of individual style of professional activity the author understands the individual, peculiar system of psychological means to which a person manages in order to balance his personality with the external conditions of activity. In this case the individual style of professional activity of policemen is considered as a strategy of behavior in the work activity determined by the individual characteristics of the subject of activity. The emphasis is on the factors that shape the personal style of professional activity that are mainly due to the peculiarities of the nervous system and personal characteristics. After all, the work of police officers has its own specifics and is carried out under extreme conditions. So, without possessing the psychological characteristics and individuality properties they can not be effective employees. An attempt was made to determine the structure of the individual style of professional activity as a holistic entity, namely: functions, attributes, levels and components. It is indeed important and necessary to form the individual style of professional activity of police officers to develop their personality and to achieve a professional and personal integrity as a subject of effective work behavior. Since, it is significantly affects the importance of the process of professional-psychological support and the selection of qualified future professionals.